Pengembangan LKPD Berbasis Realistic Mathematics Education pada Materi Bangun Datar di Kelas IV SDN 03 Tiumang - Eka Filahanasari; Nurul Hidayah Fitriyani; Suci Rahma Putri (Universitas Negeri Padang, 2022)
This study aims to describe the development steps and saw the feasibility of a student worksheet that is used as a learning media. This type of research was development research with development procedures using the ADDIE model. The development procedure consisted of analysis, validation of performance gaps, product design, validation of media experts and material experts, individual trials, group trials, and implementation. Subjects were students of class VI.B SDN 03 Tiumang. The other instruments were validation sheets for media and material experts, teacher assessment sheets, student assessment sheets. Results of the research found the student worksheet learning media developed was valid in terms of the media expert's assessment which score percentage of material validation was 82,3%. Student worksheet learning media developed practically reviewed assessment of teacher questionnaire was a score of 3,75 and the average score of student assessment questionnaire of 3,625. Student worksheet learning media developed was effectively reviewed from pre-test score 50,5 and post-test 72,75. The results test sample paired obtained a value of significance of as much as 0.00 which means there was significant influence by the presence of the uses of student worksheet learning media.